Efeitos da ativação da enzima conversora de angiotensina 2 endógena no glaucoma experimental em ratos - Giselle Foureaux Heida (2013)
The purpose of this study was to evaluate the effects of the activation of endogenous angiotensin-converting enzyme 2 (ACE2) using the compound diminazene aceturate (DIZE) in an experimental model of glaucoma in Wistar rats. DIZE (1mg/kg) was administered daily either systemically or topically, and the intraocular pressure (IOP) was measured weekly. To examine the role of the Mas receptor in the effects of DIZE, the Ang-(1-7) antagonist A-779 was coadministered. Drainage of the aqueous humor was evaluated by using scintigraphy. The analysis of ACE2 expression by immunohistochemistry and the counting of retinal ganglion cells (RGCs) were performed in histological sections. Additionally, the nerve fiber structure was evaluated by transmission electron microscopy. In addition, chitosan films containing DIZE were developed for controlled release of the compound and placed in the conjunctival fornix of the animals. The systemic and topical administration (in the form of eye drops) of DIZE increased the ACE2 expression in the eyes and significantly decreased the IOP of glaucomatous rats without changing the blood pressure. Importantly, this IOP-lowering action of DIZE was similar to the effects of dorzolamide. The antiglaucomatous effects of DIZE were blocked by A-779. Histological analysis revealed that the reduction in the number of RGCs and the increase in the expression of caspase-3 in the RGC layer in glaucomatous animals were prevented by DIZE. This compound also prevented alterations in the cytoplasm of axons in glaucomatous rats. In addition to these possible neuroprotective effects, DIZE facilitated the drainage of the aqueous humor. Chitosan films containing DIZE were well tolerated by the animals and were effective in reducing IOP for 30 days utilizing the amount of the compound used in a single dose of the topical treatment. Our results evidence the pathophysiological relevance of the ocular ACE2/Ang-(1-7)/Mas axis of the renin-angiotensin system and, importantly, indicate that the activation of intrinsic ACE2 is a potential therapeutic strategy to treat glaucoma